Picard Sequence and Fixed Point Results on b-Metric Spaces. (25th February 2015) - Demma, Marta; Vetro, Pasquale
Abstract : We obtain some fixed point results for single-valued and multivalued mappings in the setting of ab -metric space. These results are generalizations of the analogous ones recently proved by Khojasteh, Abbas, and Costache.